2020
DOI: 10.1016/j.ifset.2020.102288
|View full text |Cite
|
Sign up to set email alerts
|

High-voltage pulsed electric field laboratory device with asymmetric voltage multiplier for marine macroalgae electroporation

Abstract: Optimization of protocols is required for each specific type of biomass processed by electroporation of the cell membrane with high voltage pulsed electric fields (PEF). Such optimization requires convenient and adaptable laboratory systems, which will enable determination of both electrical and mechanical parameters for successful electroporation and fractionation. In this work, we report on a laboratory PEF system consisting of a high voltage generator with a novel asymmetric voltage multiplying architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 53 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…For example, Grainys et al have developed a high-voltage, bipolar electroporator that generates single or multiple, symmetrical or asymmetrical, high-power square wave microsecond pulses up to ±1 kV and 100 A (113). Levkov et al reported on a PEF system consisting of a high-voltage generator with an asymmetric voltage multiplying architecture and a treatment chamber with sliding electrodes for marine macroalgae electroporation (114). The system enables pulses of up to 4 kV and 1 kA with a pulse duration between 1 ms and 100 ms.…”
Section: Asymmetric Pulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Grainys et al have developed a high-voltage, bipolar electroporator that generates single or multiple, symmetrical or asymmetrical, high-power square wave microsecond pulses up to ±1 kV and 100 A (113). Levkov et al reported on a PEF system consisting of a high-voltage generator with an asymmetric voltage multiplying architecture and a treatment chamber with sliding electrodes for marine macroalgae electroporation (114). The system enables pulses of up to 4 kV and 1 kA with a pulse duration between 1 ms and 100 ms.…”
Section: Asymmetric Pulsesmentioning
confidence: 99%
“…Levkov et al. reported on a PEF system consisting of a high-voltage generator with an asymmetric voltage multiplying architecture and a treatment chamber with sliding electrodes for marine macroalgae electroporation ( 114 ). The system enables pulses of up to 4 kV and 1 kA with a pulse duration between 1 μs and 100 μs.…”
Section: Asymmetric Pulsesmentioning
confidence: 99%
“…The custom-made HVPG electric device used in this study was described in detail in our previous works. 15,30,34 The functional scheme of the HVPG is presented in Figure 2a, and the design of the HVPG is shown in Figure 2b; the interaction of functional units is described in the work algorithm of the device. The novel mechanical parts of the continuous PEF device especially designed and constructed in this study are shown in Figure 3.…”
Section: Experimental Designmentioning
confidence: 99%
“…However, all PEF studies known to us on seaweeds have been done in batch systems. , PEF process development on other types of biomasses showed that the transition from batch to continuous processes, which is desirable for the industry, is possible but challenging . Among many challenges, there is a need for equipment development for a continuous PEF process and for process condition optimization .…”
Section: Introductionmentioning
confidence: 99%
“…In fish processing, PEF treatment is also applied to improve the extraction of various organic compounds from fish and seafood [180][181][182][183]. Franco et al (2020) [184] recommended the use of PEF treatment for improved antioxidant extraction from fish residues (gills, bones, and heads) of two commercial species (sea bream and sea bass).…”
Section: Effects Of Pef On the Quality Of Fish And Seafoodmentioning
confidence: 99%